Problems in Family Business : Systematic Literature Review (SLR) - Amenah Amenah; Maghfiroh Maghfiroh; Ludi Wishnu Wardana; Aniek Indrawati; Bagus Setiawan (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
This family business is very important for survival and influential in the country, the high unemployment rate that exists in this country makes family business one of the opportunities in creating jobs. Several studies on family businesses have noted the very significant role of family businesses in a country's economic growth. Gender roles in family companies, especially in Indonesia, are very important. In addition to gender, there are other indicators related to problems in a family business, from several articles that have been found including business strategy, communication and the role of a woman in a family business. From several articles reviewed, the majority of the research used a qualitative approach in discussing problems in family businesses. This is because in this theme detailed research is needed through interviews conducted with respondents who know and have a family business.